1994
DOI: 10.1111/j.1558-5646.1994.tb02185.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence

Abstract: Abstract. -Why do parasites harm their hosts? Intuition suggests that parasites should evolve to be benign whenever the host is needed for transmission. Yet a growing theoretical literature offers several models to explain why natural selection may favor virulent parasites over avirulent ones. This perspective first organizes these models into a simple framework and then evaluates the empirical evidence for and against the models. There is relatively scant evidence to support any of the models rigorously, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
223
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(226 citation statements)
references
References 68 publications
2
223
0
1
Order By: Relevance
“…However, research using other host-parasite system has shown that life history characteristics related to parasite transmission are intimately linked with virulence; those parasites that are transmitted faster presumably become more virulent (Garnick 1992;Bull 1994;Ebert and Herre 1996;Frank 1996;Day 2001). In fact, while most scientists define virulence as the extent of damage or death caused to a host (Ewald 1994), others have observed that virulence is a property of both host and parasite (Bull 1994;Poulin and Combes 1999). Thus, Garnick (1992) referred to virulence as the ability to develop and reproduce in a host, and Poulin and Combes (1999) remarked that studies of virulence must emphasize the ability of the parasite to multiply.…”
Section: Discussionmentioning
confidence: 99%
“…However, research using other host-parasite system has shown that life history characteristics related to parasite transmission are intimately linked with virulence; those parasites that are transmitted faster presumably become more virulent (Garnick 1992;Bull 1994;Ebert and Herre 1996;Frank 1996;Day 2001). In fact, while most scientists define virulence as the extent of damage or death caused to a host (Ewald 1994), others have observed that virulence is a property of both host and parasite (Bull 1994;Poulin and Combes 1999). Thus, Garnick (1992) referred to virulence as the ability to develop and reproduce in a host, and Poulin and Combes (1999) remarked that studies of virulence must emphasize the ability of the parasite to multiply.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in spite of quarantine controls, infested commercial colonies have been introduced to some countries (Goka et al, 2001). Following interspecific transmission of parasites, virulence on new hosts could be higher or lower, although more noticeable in the former case (Bull, 1994). Furthermore, it is postulated that the sudden decline of five North American bumblebee species might be related to N. bombi outbreak in bumblebee facilities that decimated the commercial colonies of B. occidentalis (Thorp and Shepherd, 2005;Winter et al, 2006;Williams and Osborne, 2009).…”
Section: Transmission Of Pathogensmentioning
confidence: 99%
“…However, the vast majority of fungal viruses have little or no detectable effect on host phenotype or fitness (Buck, 1986(Buck, , 1998Ghabrial, 1998;Ghabrial and Suzuki, 2009;McCabe et al, 1999;Pearson et al, 2009). The "conventional wisdom" about virulence is that associations persisting for a long time should evolve to being benign or even beneficial, and particularly so for pathogens that depend primarily on vertical transmission to host offspring (Bull, 1994;Levin, 1996). A pathogen that depends on vertical transmission and adversely affects the fitness of its host (i.e., virulence) will, on average, reduce its own fitness because vertical transmission will be reduced; in this case, therefore, virulence will be selected against.…”
Section: Effects Of Viruses On Fungal Fitnessmentioning
confidence: 99%